PEMBERIAN PUPUK PELENGKAP CAIR (PPC) BAYFOLAN PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) MENGGUNAKAN MEDIA TANAH SALIN DI PEMBIBITAN UTAMA - Wan Firzariska Noor; Ardian Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Research on palm oil plant seeds using saline soil media has never been discouraged doing, therefore conducted research using saline soils by providing complementary liquid fertilizer treatment bayfolan. Fertilizer application through the leaves was conducted to determine the effect of fertilizer and to find the best fertilizer concentrations in the medium saline soil on the growth of seedlings of oil palm plantations. The experiment has been conducted in the station Faculty of Agriculture, Riau University, Pekanbaru from May 2016 to August 2016. This study used a completely randomized design consisting of 6 levels p0: 0 ml/l air, p1: 1 ml/l air, p2: 2 ml/l air, p3: 3 ml/l air, p4: 4 ml/l air and p5: 5 ml/lair. Data were statistically analyzed by analysis of variance, then the results followed with honestly significant difference test (BNJ) at 5%. Parameters measured were analysis of soil chemical properties, increase seedling height, increase the number of leaf midrib, increase in diameter hump, root volume, the ratio of the canopy and root and seedling dry weight. The results showed that the effect of fertilizer complementary liquid with different concentrations in the medium saline soil does not produce any real effect on the parameters of observation, only the parameters in the number of leaf midrib and dry weight were influential real and fertilizer complementary liquid with a concentration treatment 3 ml/l water results the highest growth ib the medium of oil palm seedlings to copy from the age of 3 months to 6 months. Keywords :Oil Palm Seedlings, Saline Soils, Fertilizers Liquid Complementary Bayfolan